Antibiotic resistance profile of Enterococcus spp. strains isolated from the intestinal tract at the Yaounde Military Hospital Laboratory - Serge Damase Oyong Assiene; Celestin Roger Ayangma; Cedric Gueguim; Dieudonné Adiogo; Esther Ngah; Armel Julien Agamou Assiene (GSC biological and pharmaceutical sciences, 2022)
Multidrug-resistant Enterococci colonizing the intestinal tract of patients are the major sources of infection as well as the spread of resistance. The present study aims to determine the antimicrobial resistance profile of Enterococcus species from the intestinal tract of patients admitted to the laboratory of the Yaounde Military Hospital. The study was conducted in patients from July to November 2020. Stool samples were collected and processed for bacterial isolation and antimicrobial susceptibility testing. Stool samples were inoculated onto selective Enterococci media (Bile Esculin azide agar). The isolates obtained were identified to the level of genus and species level: characteristics, Gram staining and use of API 20 Streptococcus system. Susceptibility testing was performed using the Kirby-Bauer solid state disk diffusion method. Of the 35 samples analyzed 19 strains were isolated, 9 Enterococci and 10 non-Enterococci. Enterococci were isolated from 9 (25.7%) of the study subjects. The isolates were Enterococcus faecium (36.9%) followed by Enterococcus faecalis (10.5%), Aerococcus viridans (31.5%), Streptococcus mitis 1 (10.5%) and finally Streptococcus mitis 2 (10.5%). Of the 9 Enterococci isolates tested, 6 (66.6%) were resistant to Ampicillin, 9 (100%) to Gentamycin and 4 (44.4%) to Amikacin. Other alternative antibiotics to treat infection that may be caused by Enterococci have also shown a high rate of resistance in vitro: levofloxacin 6 (66.6%), erythromycin 8 (88.8%), tetracycline 7 (77.7%), chloramphenicol 4 (44.4%). 7 (77.7%) of the Enterococci were resistant to vancomycin. Multidrug resistance was predominant in E. faecium up to R7 (10.5%), however multi resistance was more pronounced at R3 (94.73%). This study reveals a high rate of faecal colonization by multidrug-resistant Enterococci and an increasing prevalence of strains resistant to vancomycin. Thus, periodic monitoring of antibacterial susceptibilities is recommended to detect emerging resistance and prevent the spread of multi-resistant bacterial strains.